STRATEGIES FOR DEVELOPING HAJJ AND UMRAH TRAVEL IN THE PANDEMIC ERA: A STUDY BY DUTARIZKIA TOUR AND TRAVEL IN DEPOK - Fitria Destiana Fitria (Jurnal Dakwah Tabligh, 2022)
The results of the analysis concluded that Depok and Umrah Tour and Travel applied word-of-mouthstrategy as the main strategy, applying geographic segmentation, demographic segmentation, andpsychographic segmentation as a mapping strategy; single-focus (niche) marketing targeting strategy; andpositioning strategy is “best service”. Mixed with marketing mix theory (1) product: formulating a newproduct, namely gold savings; (2) price: “at the market”; (3) promotion: actively using social media andmaintaining relationships with alumni and partners; (4) distribution: housing and services forimplementing employees can be carried out at the office or at home visits. Dutarizkia Tour and Travelformulates to serve products that are useful for prospective pilgrims. This activity is supported bypromotions on social media and continuing ongoing relationships with alumni and partners.